A dendrite-free and stable anode for high-performance Li–O2 batteries by prestoring Li in reduced graphene oxide coated three-dimensional nickel foam. Issue 55 (10th June 2020) - Zhao, Huimin; Ma, Yiru; Qi, Haocheng; Xiao, Zhenyu; Lin, Haifeng; Liu, Jie; Guo, Ziyang; Wang, Lei; Feng, Shouhua
Abstract : GO modified Ni foam is used as a host to construct a Li/rGO-Ni electrode, which suppresses dimensional changes and Li dendrites. Abstract : Li-based reduced (r)GO-Ni (Li/rGO-Ni) was prepared by a thermal-infusion method. Li/rGO-Ni based symmetric cells have high cycling stability and small voltage hysteresis at various current densities. Furthermore, the Li/rGO-Ni based Li–O2 batteries exhibit good performances.